Potential Elimination of Chromium (VI) by Chemically Biochar Derived from Pennisetum Setaceum - Nguyen, My Linh (Journal of Technical Education Science, 2022)
This study consisted of a novel potential adsorbent material that could efficiently remove chromium (VI) from aqueous solutions. The optimum operating conditions were investigated including pH, agitation period. In this research, biochar derived from fountain grass (Pennisetum setaceum) coated with glutaraldehyde-crosslinked chitosan and treated with succinic acid to add functional groups was used to create an eco-friendly sorbent (CPES). It demonstrated that 3.0 is the ideal pH for the Cr (VI) adsorption process. The equilibrium stirring time is 120 minutes. The Langmuir and Freundlich models have been used to examine experimental data. According to the results, and the Freundlich model performed a better fit of the result than the Langmuir one. Cr (VI) has a maximum adsorption capacity of 30.96 mg/g. The Gibbs free energy change (êG), enthalpy change (êH), and entropy change (êS) thermodynamic parameters were determined. The fact that êG was negative demonstrated that Cr (VI) adsorption onto the CPES adsorbent occurred spontaneously.